Impact of Salt-tolerant Rootstock on the Enhancement of Sensitive Tomato Plant Responses to Salinity - Çoban, Ayşe; Akhoundnejad, Yelderem; Dere, Sultan; Daşgan, Hayriye Yıldız (AMER SOC HORTICULTURAL SCIENCE, 2020)
. In the present study, salt-tolerant (Tom 174) and sensitive (Tom 121) tomato genotypes were grafted onto their own roots (174/174 and 121/121), and a susceptible genotype was also grafted onto tolerant genotype 121/174. The grafted plants were grown under 50 mM NaCl and control conditions in a greenhouse. Plant physiological parameters, fruit yield, and physical measurements of fruit (e.g., weight, height, diameter, volume), and chemical analysis of fruit (e.g., vitamin C, pH, and total dry matter content) were investigated. When the sensitive genotype was grafted onto tolerant genotype 121/174, the tolerant genotype Tom 174 reduced the yield loss of susceptible genotype from 44% to 3%. Also, fruit size, total dry matter content, and vitamin C increased, while pH decreased under saline conditions. The rootstock Tom 174 seemed to be able to control sensitive scions’ stomatal openness and closure for transpiration and CO2 transition on photosynthesis because dry matter content was increased. It was found that the tolerant genotype played a role in ameliorating leaf osmotic adjustment of the sensitive genotype in grafting under salt stress. The combination 121/174 had the lowest Na+ concentration in young leaves. Thus, the tolerant rootstock Tom 174 decreased the transport of accumulation of Na+ ions to young leaves in this grafting combination.
Keywords: Grafting; NaCl stress; Solanum lycopersicum; Tolerance; Rootstock